Контролінг: сучасні методи та інструментарій - Єршова, Наталя Юріївна; Денисова, Н. Ю. (НТУ "ХПІ", 2010)
In article the basic methods of controlling at the modern enterprises are examined, the basic analytical stages Benchmarking as one of methods of controlling are formulated. It is lead calculation of quantitativecriterion for division ofthe enterprises into groups at carrying out Benchmarking by means of the discriminantal analysis with the purpose of improvement of quality of the analysis.
Keywords: концепція управління; політика облікова; практика управлінська; звітність внутрішня; планування довгострокове